Analysing Everyday Sound Environments: The Space, Time and Corporality of Musical Listening. (December 2014) - Nowak, Raphaël; Bennett, Andy
This article develops the notion of 'sound environment' as a new way of theorizing the relationship between music, audiences and everyday life. The article draws on findings from an empirical case study conducted with young people between the ages of 21 and 32. In focusing on this age range, we consider 'mundane' music consumption practices in contrast to the more 'spectacular' forms of youth cultural music consumption often documented in academic work. In an age characterized by the increasing omnipresence of music, young people hear or listen to music in various configurations, for example, by mobilizing a particular music technology and content or hearing music while shopping in a department store, visiting a friend at home, or travelling in an elevator. Drawing on the concept of the 'sound environment', this article looks at variables of space, time and body to explain the contextualization of music in everyday life.